Pengembangan Lembar Kerja Siswa Berbasis Model Discovery Learning pada Pokok Bahasan Sudut Kelas VII - Selly Noviafitri; Somakim Somakim; Yusuf Hartono (Universitas Hamzanwadi, 2016)
The research aims to produce a valid and practical LKS based on discovery learning model and also having potential effect. This type of research is Development Study of Design Research. The subject of this research were the first year students of SMP Negeri 7 Prabumulih academic year 2015/2016. The technic of collecting data have done with walkthrough, test, observation, and interview. The result of this research was produce two LKS that valid and practical based on discovery learning model with characteristic (1) Contain stages of discovery learning model, (2) Assist students in finding concepts on the subject of the angle, (3) make students being actively in learning process .Valid can be seen from the result of validator assessment where the validator comment on the first prototype of LKS from content, construct, and language perspective. Practical can be seen from the result of small group try out, which is based on analysis of the answer sheets of students found that students are able to complete each stage there, and based on coment sheet of students found that LKS given were easy to used and understanded by students. This devoloved LKS which based on discovery learning model also have the potential effect toward result study. The result study from this research consisted of cognitive domain, affective domain, and psychomotor domain. In the cognitive domain, 91,66% of students got score more than 6,25, in the affective domain, all students have demonstrated a responsible attitude and respect that seen from the observation during LKS usage, and the psychomotor domain, all of students have been skilled that seen from the result of students performance.